Circadian rhythms in the morphology of neurons in Drosophila. - Mehnert, K.I.; Cantera, R. (Cell and Tissue Research, 2011)
Neurons have an enormous capacity to adapt to changing conditions through the regulation of gene expression, morphology, and physiology. In the fruit fly Drosophila melanogaster, this plasticity includes recurrent changes taking place within intervals of a few hours during the day. The rhythmic alterations in the morphology of neurons described so far include changes in axonal diameter, branching complexity, synapse numbers, and the number of synaptic vesicles. The cycles of these changes have larger amplitude when the fly is exposed to light, but they persist in constant darkness and require the expression of the clock genes period and timeless, leading to the concept of circadian plasticity. The molecular mechanisms driving these cycles appear to require the expression of these genes either inside the neurons themselves or in other peripheral pacemaker cells. Loss-of-function mutations in period and timeless not only abolish the morphological rhythms, but also often cause abnormal axonal branching suggesting that circadian plasticity is relevant for the maintenance of normal morphology. Research into whether (1) circadian plasticity is a common feature of neurons in all animals and (2) our own neurons change shape between day and night will be of interest.